El Caballo Cracker de Florida - Jorge R. Rey (EDIS, 2009)
AN219SP, a 4-page illustrated fact sheet by Jorge Rey, is the Spanish language version of AN216: The Florida Cracker Horse. It describes this small breed of saddle horse designated “Florida’s Heritage Horse” by the Florida Legislature in 2008 — breed characteristics, history, current status, and events. Includes references. Published by the UF Department of Animal Sciences, June 2009. Revised June 2012.